2004
DOI: 10.1038/sj.gt.3302322
|View full text |Cite
|
Sign up to set email alerts
|

Local adenoviral expression of Fas ligand upregulates pro-inflammatory immune responses in the CNS

Abstract: The central nervous system (CNS) is a site of relative immunological privilege; despite this it can be a target of the immune system under certain conditions. For example, adenoviral vectors elicit an immune response strong enough to result in antigen elimination, in immunologically primed animals. Fas ligand (FasL) contributes to the immune privilege of certain tissues by inducing apoptosis in activated T cells. We therefore investigated whether local overexpression of FasL could downregulate the immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…17 The adenovirus-mediated expression of FasL also is abrogated in a relatively short time (~14 days) because the transduced cells are killed as a consequence of the inflammatory response. 33 Therefore, both mechanisms (Fas-mediated apoptosis and inflammation leading to tumor cell death) minimize persistence of FasL in the system. The most commonly observed toxicities were transient increases in aspartate transaminase and creatine phosphokinase.…”
Section: Discussionmentioning
confidence: 99%
“…17 The adenovirus-mediated expression of FasL also is abrogated in a relatively short time (~14 days) because the transduced cells are killed as a consequence of the inflammatory response. 33 Therefore, both mechanisms (Fas-mediated apoptosis and inflammation leading to tumor cell death) minimize persistence of FasL in the system. The most commonly observed toxicities were transient increases in aspartate transaminase and creatine phosphokinase.…”
Section: Discussionmentioning
confidence: 99%
“…However, marked inflammatory lesions were detected mostly in the surrounding areas of tumours in animals treated with the combination of FasL and etoposide and not in untreated rats. These lesions could be related to the inflammatory activity of FasL through chemokines and IL-1 release (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Systemic as well as intraparenchymal delivery of viral vectors usually induces humoral and cell-mediated immune responses against the vectors and/or transgene products, leading to inflammation, short-term persistence of gene expression and elimination of transduced cells. [5][6][7] We, and others, have previously shown that injection of viral vectors into the cisterna magna, or trough lumbar puncture, might represent an efficient CNS delivery system in both small (mice) and large (non-human primates) animals. [8][9][10][11] Administration of vector into the cerebrospinal fluid (CSF) circulation, while bypassing the blood-brain barrier, allows viral vector transduction of neuroepithelial cells and delivery of transgene products to the whole CNS through the ventricular circulation.…”
Section: Introductionmentioning
confidence: 99%